The Potency of Kuldon® Solution in The Healing Process of Aphthous Stomatitis - Dewi Priandini; Alfred Pakpahan; Rahmi Amtha; Aprilia Puspita Sulistia; Abrijanto Abrijanto (Biology, Medicine, & Natural Product Chemistry, 2025)
Objectives: This study aimed to assess the efficacy of Kuldon® solution in the healing process of aphthous stomatitis.  Methods: A double-blind randomized controlled trial was conducted involving 60 subjects (27 males, 33 females), randomly assigned to receive either Kuldon® solution (Drug A) or hyaluronic acid rinse (Drug B). Pain was evaluated using the Visual Analogue Scale (VAS), and lesion diameter was measured on days 2, 5, and 7. Data were analyzed using the Mann-Whitney test (p < 0.05). Results: Drug A showed a greater reduction in pain and lesion size compared to Drug B. By day 5, 100% of Drug A users reported no pain, with 90% showing lesion reduction.Conclusion: Kuldon® solution demonstrates significant therapeutic potential in managing aphthous stomatitis.